The Application of Artifical Inteligence in Breast Cancer Prevention and Early Detection - Ivković, Andjela; Jevtić, Marija; Barać, Dušan (E-business technologies conference proceedings, 2025)
This paper discusses the technological aspects of Artificial Intelligence, Machine Learning, and Deep Learning, and the potential of their application in the early detection and prevention of breast cancer. To gain a complete overview of the potential utilization, the paper highlights the critical challenges in oncology care today through various stages of the patient journey – screening, diagnosis, staging, treatment planning, and therapy outcome prediction. The goal is to identify the bridge between the pain points of preventing and diagnosing breast cancer and the core functionalities of AI systems, such as detection, classification, characterization, and risk stratification. The research indicates that the impact of integrating AI in oncology care is significant and highlights the benefits of collaborative work between healthcare professionals and AI to achieve more precise diagnosis, evaluate the future risk with more certainty, screen more potential breast cancer patients in the same timeframe, and address healthcare communication problems.